Perancangan dan Implementasi Aplikasi Manajemen Inventaris Toko Berbasis Desktop Menggunakan Python dengan Pendekatan Pemrograman Berorientasi Objek (OOP) - Rosma Siregar; Ratih Tri Elsadin; Fatma Asisah; Yosa Steven Perangin Angin; Abel Frans Lamsihar Sinaga (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
In the age of modern technology, effective inventory management is an essential part of business operations. Many small businesses, especially MSMEs, continue to use manual methods that have a high risk of data errors. The purpose of this research is to create a desktop-based application for inventory management called Stock Track that uses the Python programming language and Object Oriented Programming (OOP) approach. Recording items, monitoring stock, and generating reports that help decision-making are all features that this application has. Research shows that the app helps manage inventory more efficiently and reduces reliance on manual record-keeping. Stock Track is designed to help store owners manage their stock in a more organized and accurate manner with a user-friendly user interface.